Glomerular capillary C3 deposition as a risk factor for unfavorable renal outcome in pediatric primary focal segmental glomerular sclerosis - Peng, Yingchao; Li, Banghai; Li, Xiaojie; Ju, Tao; Zhang, Zhiqiang; Wang, Peipei; Sun, Tao; Shu, Jiaping; Wang, Meiqiu; Sun, Xiaoyi; Chen, Huangyu; Gao, Chunlin; et al. (Frontiers in Pediatrics, 2023)
Introduction: Some patients with primary focal segmental sclerosis (FSGS) demonstrate complement 3 (C3) deposition in glomerular capillary loops (Cap-C3) and/or mesangial area (Mes-C3). The clinicopathological and prognostic significance of C3 deposition remains incompletely investigated, especially in the pediatric cohort. Methods: We retrospectively analyzed 264 children of biopsy-proven primary FSGS between January 2003 and December 2020. The correlation between Cap-C3 and the renal outcome was evaluated by the Kaplan-Meier method and Cox multivariate regression analysis. Renal end-point event was defined as the development of end-stage renal disease, death for renal disease, or an estimated glomerular filtration rate reduction by at least 50% from baseline. Results: Among the 264 patients, 30 (11.4%) had Cap-C3. Kaplan-Meier analysis showed that patients with Cap-C3 had significantly lower renal survival rates than patients without Cap-C3 (60.17% vs 84.71% at 5 years, 39.49% vs 65.55% at 10 years, P ＜0.01). Cox multivariate regression analysis showed that Cap-C3 was an independent risk factor for the poor renal outcome (HR 3.53, 95% CI 1.22-10.19, P =0.02). Conclusions: Glomerular capillary C3 deposition was an independent risk factor for unfavorable renal outcome in children with primary FSGS.